Fast Solution-Phase and Liquid-Phase Peptide Syntheses (SolPSS and LPPS) Mediated by Biomimetic Cyclic Propylphosphonic Anhydride (T3P®) - Alexia Mattellone; Dario Corbisiero; Paolo Cantelmi; Giulia Martelli; Chiara Palladino; Alessandra Tolomelli; Walter Cabri; Lucia Ferrazzano (Molecules, 2023)
The growing applications of peptide-based therapeutics require the development of efficient protocols from the perspective of an industrial scale-up. T3P® (cyclic propylphosphonic anhydride) promotes amidation in the solution-phase through a biomimetic approach, similar to the activation of carboxylic moiety catalyzed by ATP-grasp enzymes in metabolic pathways. The T3P® induced coupling reaction was applied in this study to the solution-phase peptide synthesis (SolPPS). Peptide bond formation occurred in a few minutes with high efficiency and no epimerization, generating water-soluble by-products, both using N-Boc or N-Fmoc amino acids. The optimized protocol, which was successfully applied to the iterative synthesis of a pentapeptide, also allowed for a decrease in the solvent volume, thus improving process sustainability. The protocol was finally extended to the liquid-phase peptide synthesis (LPPS), where the isolation of the peptide was performed using precipitation, thus also showing the suitability of this coupling reagent to this emerging technique.